1987
DOI: 10.1038/bjc.1987.205
|View full text |Cite
|
Sign up to set email alerts
|

The reactivity of alpha-1-antitrypsin with Lens culinaris agglutinin and its usefulness in the diagnosis of neoplastic diseases of the liver

Abstract: Summary The reactivity of alpha-l-antitrypsin (AAT) with Lens culinaris agglutinin (LCA) was studied by crossed immuno-affinity electrophoresis of the sera of 246 subjects from 6 groups (acute virus hepatitis, chronic hepatitis, liver cirrhosis, hepatocellular carcinoma (HCC), carcinoma metastatic to the liver and normal controls). Two species of AAT (LCA-reactive and -nonreactive species) were detected on crossed immuno-affinity electrophoresis in a gel containing LCA. The percentages of LCA-reactive species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…Our previous results, as well as the results of other reports, show that measurement of the Lens culinaris agglutinin (LCA)‐reactive species of AFP is useful for such discrimination and that the molecular basis of this variation is the fucosylation at the innermost N‐ acetylglucosamine residue of a biantennary sugar chain 8 –14 . We also reported that LCA‐reactive species of alpha‐1‐antitrypsin (AAT) and transferrin (TF) might provide useful information for the diagnosis of patients with HCC 15 –17 . This suggests that the degree of fucosylation of serum glycoproteins is a useful measurement for the diagnosis of HCC.…”
Section: Introductionmentioning
confidence: 80%
“…Our previous results, as well as the results of other reports, show that measurement of the Lens culinaris agglutinin (LCA)‐reactive species of AFP is useful for such discrimination and that the molecular basis of this variation is the fucosylation at the innermost N‐ acetylglucosamine residue of a biantennary sugar chain 8 –14 . We also reported that LCA‐reactive species of alpha‐1‐antitrypsin (AAT) and transferrin (TF) might provide useful information for the diagnosis of patients with HCC 15 –17 . This suggests that the degree of fucosylation of serum glycoproteins is a useful measurement for the diagnosis of HCC.…”
Section: Introductionmentioning
confidence: 80%
“…Similar to AFP, the percentage of reactive species with the lectin Lens culinaris agglutinin was shown to be significantly higher in HCC than in benign liver diseases and normal controls [63]. Further structural analysis on the AAT-attached glycans was performed and it was shown that the fucosylated biantennary glycans were increased two-fold opposite non-fucosylated glycans [64].…”
Section: Fucosyltransferasesmentioning
confidence: 97%
“…The serum Lens culinaris agglutinin‐reactive fraction of AFP (AFP‐L3), a well‐known component of α‐fetoprotein (AFP) with a core fucose residue, is widely used for HCC diagnosis and follow‐up surveillance as a tumor serologic marker. Haptoglobin, α1‐antitrypsin and transferrin possess altered glycosylation forms in patients with HCC.…”
Section: Introductionmentioning
confidence: 99%